Fiqh of Civilization at Traditional Islamic Boarding School: Contextualizing of Islamic Jurisprudence through Classical Texts of Mu’amalat - Mustofa, Imam; Hefni, Wildani; Maliki, Ibnu Akbar; Chamdan, Umar (JURIS (Jurnal Ilmiah Syariah), 2024)
The culture of thought that is still traditionalist in most Islamic boarding schools raises questions about the relevance in the modern era. The use of yellow books as the main reference is considered extremely classic and generally in facing the complexity of modern society problems. Therefore, this study aimed to examine the contextualization of fiqh mu’amalat in the classic text of yellow book at Sidogiri Islamic Boarding School as one of the agendas of Halaqah Fiqh of Civilization. This was a qualitative study with primary data collected through observation and interview, while the secondary data was from literature studies on scientific writing references. Primary data included the results of interviews with the chairman of the supervisory board, the chairman of Bahtsul Masail, and the secretary of Islamic boarding school as well as observations of the business development activities of Islamic boarding school. Meanwhile, secondary data was in the form of written sources regarding the contextualization of fiqh mu’amalat supported by various references to books, journal articles, and other related documents. The results showed that the contextualization of fiqh mu’amalat at Sidogiri Islamic Boarding School was conducted through the elaboration of classic text (yellow book) with the reality of mu’amalat in modern society. Consistency in integrating the teachings of Salaf in the books of classical Ulema has succeeded in maintaining the application of the mu’amalat principles in every development of business units. The contextualization of fiqh Salaf started by making Bahtsul Masail an intellectual forum to answer the problems of mu’amalat in society. The results were actualized by making it a practical reference in every contract conducted in Islamic Boarding School Cooperative (Kopontren) business unit, Basmalah Store, and Baitul Mal wat Tamwil (BMT). The success of the economic empowerment confirmed that fiqh in Islamic boarding schools was not only studied dogmatically. This also showed the openness of Islamic boarding schools to accept progressive ideas in seeing new civilizations with their classical values. In conclusion, this study was expected to be an academic reference that pioneered the renewal of fiqh mu’amalat in the digital era.